2013
DOI: 10.1021/tx300395w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Permeability Transition Pore Inhibitors Prevent Ethanol-Induced Neuronal Death in Mice

Abstract: Ethanol induces brain injury by a mechanism that remains partly unknown. Mitochondria play a key role in cell death processes, notably through the opening of the permeability transition pore (PTP). Here, we tested the effect of ethanol and PTP inhibitors on mitochondrial physiology and cell viability both in vitro and in vivo. Direct addition of ethanol up to 100 mM on isolated mouse brain mitochondria slightly decreased oxygen consumption but did not affect PTP regulation. In comparison, when isolated from et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…The cell death and behavioral changes were attenuated by blockade of mPTP opening. 57 This was of interest since ethanol and propofol both act on the GABA A receptor in the brain. The role of mPTP opening and the link between mitochondrial fission and the mPTP has yet to be studied in anesthetic-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell death and behavioral changes were attenuated by blockade of mPTP opening. 57 This was of interest since ethanol and propofol both act on the GABA A receptor in the brain. The role of mPTP opening and the link between mitochondrial fission and the mPTP has yet to be studied in anesthetic-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…28 Inhibition of mPTP opening has been shown to attenuate ethanol-induced neurotoxicity in mice. 29 However, the role of mPTP opening and its connection to mitochondrial fission in propofol-induced neurotoxicity has yet to be studied. The aim of this study was to dissect the role of mitochondrial dynamics and mPTP opening in propofol-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy ethanol drinking is thought to result in adverse effects on the brain [5,8,10,19,25]. Among these effects, ethanol may alter the metabolism of some brain fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are major targets for ethanol toxicity in different tissues [4,10,13], including the brain [8,10,13]. Oxidative stress due to ethanol metabolization causes extensive degradation and depletion of brain, heart, liver, and skeletal muscle mitochondrial DNA (mtDNA) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, during synaptic process, ATP production and calcium buffering capacity produced by mitochondria are critical [18,19]; therefore, mitochondrial injury may have severe consequences on neuronal communication.In fact, evidence suggests that ethanol produces catastrophic changes in the mitochondria of organs such as liver [20] and heart [21], and over the last decade, many studies have reported the toxicity of ethanol to the brain's mitochondria [22,23]. Briefly, ethanol increases ROS production [23], alters mitochondrial respiration [23,24], impairs ATP production [22, 25], and eventually induces cell death by opening the mitochondrial permeability transition pore (mPTP) [26], observed both in vitro and in vivo [27].In this chapter, we will discuss the effects of ethanol toxicity in the brain, focusing on the mitochondria. We will describe the specific ethanol-induced alterations to mitochondrial integrity, dynamics, and bioenergetics in different scenarios of ethanol exposure including:1.…”
mentioning
confidence: 99%